Konflik Kepentingan Dalam Kebijakan Dividen - Adnyani, Ida Ayu Ary Putri; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 33 No 11 (2023)DO - 10.24843/EJA.2023.v33.i11.p01, 2023)
Dividends are part of the profits earned by the company and are announced to shareholders. Company shares can be owned by national institutions, foreign institutions, and the public. This research aims to obtain empirical evidence of the influence of national institutional ownership, foreign institutions, public ownership and debt policy on dividend policy. There are 37 sample companies with 130 sample observations from 77 manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2015-2019. The sampling technique used was purposive sampling. The data was analyzed using multiple regression, and it was found that national institutional ownership and foreign institutional ownership had a negative effect on dividend policy. The results support the tax preference theory and the client effect theory, but do not support the bird in the hand theory. Meanwhile, public ownership and debt policy have no effect on dividend policy. Keywords : Dividend Policy; National Institutional Ownership; Foreign Institutional Ownership; Public Ownership; Debt Policy.